The Spirit of Migrancy: Mati Diop’s Atlantique - Gigi Adair (Studies in 20th & 21st Century Literature, 2022)
Contemporary migration to Europe affects and involves the migrants themselves, the European host communities that receive them, and the people and communities left behind in the homelands of the migrants. Nonetheless, the impact of migration on the latter receives much less attention, both in media and political discussions of migration and in migration studies research. In this essay, I examine the depiction of migration to Europe, its causes and consequences, in the 2019 film Atlantique (Atlantics) by Mati Diop. The film, set in Dakar, Senegal, contextualizes contemporary migration from West Africa to Europe by depicting some of the economic and social causes of migration, implying a continuity between the labor exploitation effected by global neoliberalism and the European border regime and the historical exploitation of slavery and European imperialism. This genre-crossing work draws upon the cinematic traditions of ghost, zombie and detective films, and the cultural traditions of West African spirit possession and Islamic djinns to explore broader impact of migration and the highly gendered nature of the experience of migrancy in West Africa. It focuses on a group of young women left behind by migrant men who enact a quest for justice and form a community of female solidarity that enables them to envision an alternative future.
Keywords: Mati Diop; migration; Senegal; African cinema; neoliberalism; futurity